A Murine 5-Fluorouracil-Based Submyeloablation Model for the Study of Bone Marrow-Derived Cell Trafficking in Reproduction - Tal, Reshef (Endocrinology, 2016)
Bone marrow (BM)-derived cells (BMDCs) contribute to endometrial regeneration. Our objective was to develop a nongonadotoxic mouse BM transplant (BMT) model using 5-fluorouracil (5-FU) for investigating BMDCs trafficking in reproduction. Female C57BL/6J mice received either single (CTX-1) or paired (CTX-2) 5-FU (150 mg/kg) dose, or single (CTX-1+SCF) or paired-dose (CTX-3+SCF) 5-FU with stem cell factor (SCF). Control mice received BMT only or saline. BM cells (20 × 10(6)) from transgenic green-fluorescent protein (GFP) mice were injected iv. For fertility experiment, mice were mated on day 28 after BMT. Alternatively, mice were killed 1 month after BMT and BMDCs recruitment to the uterus was determined. Mice receiving 5-FU ± SCF showed intact ovarian function and fertility. CTX-3+SCF resulted in greatest BM donor chimerism at 1 month (∼45%). Flow cytometry analysis demonstrated that 6.6% of total uterine cells in CTX-3+SCF mice were GFP+ BMDCs. Remarkably, this was about 40- and 80-fold greater than BMDCs in uterus of CTX-1 or BMT only mice (6.6% vs 0.16% vs 0.08%, respectively, P < .001). Immunohistochemical analysis showed that BMDCs in the uterus were mostly localized to the endometrial stroma (71.8%). The majority of endometrial BMDCs colocalized with the pan-leuokocyte CD45 marker (58.5%), but 41.5% were CD45-negative. Cytokeratin and CD31 staining showed that the GFP+CD45− cells were not epithelial or endothelial, confirming their stromal identity. We demonstrate that paired-dose 5-FU regimen results in efficient BM donor chimerism while maintaining ovarian function and fertility. This model could be used for studying BMDCs trafficking to the uterus in various reproductive physiological and pathological conditions.